Implementation of nationwide cancer survivorship plans: Experience from the UK. (May 2018) - Maher, Jane; Petchey, Louisa; Greenfield, Diana; Levitt, Gill; Fraser, Moira
Highlights: Three-quarters of those with cancer in the UK are in the 'survivorship' stage. Problems after treatment include fatigue, pain, and bowel and bladder dysfunction. Changes to policy and practice are essential to help people to live well. National cancer strategies and survivorship initiatives have made good progress. More needs to be done, particularly for those with treatable but not curable cancer.